The Influence of Cooperative Learning Model of Group Investigation Type and First Knowledge on Mathematics Learning Outcomes of Students - abizar abizar; yantifitri fitri; hakim ramalis (Jurnal Aplikasi IPTEK Indonesia, 2019)
The purpose of this research to know the effect of teach of type in cooperative learning group investigation model Too many nouns and the effect of the first student’s knowledge in students learning in mathematics. Kind of this research that used is quasi experiment. The research sample were 24 students on experiment and students on control group. The analysis data used test- t and anova two way test. The first result of the students' mathematics learning that follows the cooperative learning model of group investigation higher than the students who follow the direct learning both seen in whole, and based on the high and low initial knowledge. Secondly, there is no interaction between cooperative learning model of group investigation type and initial knowledge in influencing student's mathematics learning outcomes.